Heterogeneous Backhaul for Cloud-Based Mobile Networks - Bartelt, Jens; Fettweis, Gerhard; Wubben, Dirk; Boldi, Mauro; Melis, Bruno (2013 IEEE 78th Vehicular Technology Conference (VTC Fall), 2013)
To meet the increasing capacity demands of future mobile networks, dense deployment of radio access nodes in combination with partly centralized processing by means of a cloud-based architecture is a promising option. In such an architecture, the design and optimization of the backhaul plays a crucial role. In this paper, we review different backhaul technologies available and discuss their characteristics for use in cloud-based networks. We point out how a heterogeneous backhaul network and a flexible centralization enables the proposed architecture and give an outlook on how a joint design of access and backhaul can help in meeting the increased demands.